The Women, Peace and Security Agenda Through a Queer Theory Lens - Jayakumar, Kirthi (Journal of Regional Security, 2022)
e two decades since the adoption of the first Security Council Resolution under the Women, Peace, and Security (WPS) Agenda has paved the way for much introspection and debate. While there have been several positive impacts such as the inclusion of women in peacemaking processes and in bringing to light the deliberate deployment of sexual violence in armed conflict as a tactic, there have also been several gaps in implementation. Since the UN Security Council passed Resolution 1325, legal, policy, and academic discourse has focused on armed conflict and women and has made an essentialist case for the inclusion of women in post-conflict peace processes. Among one of the major concerns with the WPS Agenda in its verbiage and implementation is the tendency to con ate ‘gender’ with ‘women’s issues.’ As a consequence, non-binary gender identities in general, and their experience of armed conflict in particular, have been sidelined and rendered obscure. Sexual violence in conflict has been understood through a limited ‘gender’ lens, and the unique experiences of queer people in armed conflict have neither been acknowledged or addressed in policy, legislation, and transitional justice measures. This paper critically evaluates the WPS agenda and identifies gaps both in its language and implementation through National Action Plans. It presents the unique challenges of sexual and gender minorities in armed conflict and calls for a gender, peace, and security regime founded on the principles of intersectionality, queer theory, and the right to self-determination.
Keywords: WPS Agenda; Queer Theory; conflict-related violence; peacetime-wartime continuum; LGBTQIA